Development of Rubric of Higher Order Thinking Skills Assessment on Mathematics Learning - Gradini, Ega (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
This research aims to develop a rubric of Higher-Order Thinking Skills Assessment on mathematics learning that is valid, reliable, and practical. The Plomp's developmental method, the Generic model for educational design, was deployed to develop the HOTS assessment rubric. The method consisted of 4 phases, namely; (1) preliminary investigation, (2) design, (3) development, and (4) implementation and evaluation. The rubric was designed and developed to measure students' higher-order thinking skills in mathematics learning. The rubric was developed by integrating HOTS characteristics in mathematics: critical thinking, problem-solving, mathematical understanding, mathematical modeling, proof and reasoning, mathematical representation, and mathematical communication. The HOTS assessment rubric's quality was examined using Plomp's product/prototype quality criteria: (1) validity, (2) reliability, and (3) practicality/usability. The rubric of the HOTS assessment was validated by two validators that are experts on HOTS in mathematics. The practicality/usability of the rubrics was examined by five mathematics teachers from different Junior High schools. The validity and reliability were measured using Gregory's Expert Agreement Index (EAI), while the rubric's practicality was analyzed using practicality product criteria. The research shows that the validity of the rubric of HOTS assessment on mathematics learning is 0.82 (valid), and the reliability is 0.79 (reliable). Meanwhile, the practicality of the rubric is 81.02 (Good). In conclusion, the rubric of the HOTS assessment on mathematics learning is valid, reliable, and practical to use to measure students' higher-order thinking skills in mathematics learning.